Identification of diagnostic hub genes related to energy metabolism in idiopathic pulmonary fibrosis - Zhao, S.; Sun, B. C.; Liu, N.; Huo, R.; Liu, L. S.; Wang, J. P.; Fang, C. Y. (Frontiers in Molecular Biosciences, 2025)
BackgroundIdiopathic pulmonary fibrosis (IPF) is a chronic and progressive lung disease that worsens over time, culminating in respiratory failure. Emerging evidence implicates dysregulated energy metabolism in driving fibroblast activation and extracellular matrix remodeling during IPF pathogenesis. To systematically investigate metabolic reprogramming mechanisms, we performed integrated bioinformatics analyses focusing on energy metabolism-related differentially expressed genes (EMRDEGs) and their regulatory networks in fibrotic remodeling.MethodsDifferentially Expressed Genes (DEGs) were identified by accessing datasets GSE242063 and GSE110147 from the GEO database. Energy metabolism-related genes (EMRGs) were extracted from GeneCards, followed by Venn diagram analysis to obtain EMRDEGs. Subsequent analyses included functional enrichment (GO/KEGG), protein-protein interaction network, and mRNA-miRNA, mRNA-transcription factor interaction networks. Immune infiltration analyses, including the CIBERSORT algorithm, and single-sample gene set enrichment analysis (ssGSEA), were subsequently conducted.ResultsWe identified 12 EMRDEGs and eight hub genes (ACSL1, CEBPD, CFH, HMGCS1, IL6, SOCS3, TLR2, and UCP2). Regulatory network analysis revealed HMGCS1 as a novel IPF-associated gene interacting with PPARα signaling, while SOCS3 coordinated multiple hub genes (IL6, CEBPD, UCP2, and CFH) through FOXA1/2-mediated transcriptional regulation alongside JAK/STAT3 pathway suppression. Immune profiling demonstrated significant hub gene-immune cell correlations, particularly neutrophil-mediated differential gene expression and microenvironment remodeling.ConclusionThe core EMRDEGs (HMGCS1 and SOCS3) and prioritized pathways (PPARα signaling, FOXA networks, JAK/STAT3 suppression) elucidate metabolic reprogramming mechanisms in fibrotic progression. These molecular signatures provide novel clinical biomarkers for IPF diagnosis.